Crafting Local Institution Using Social-Ecological System Framework for Sustainable Rattan Governance in Lore Lindu National Park - Yulianto; Rinekso Soekmadi; Agus Hikmat; Cecep Kusmana (Institut Pertanian Bogor (IPB University), 2019)
Rattan is the most important non-forest timber product utilized by communities adjacent Lore Lindu National Park (LLNP). The establishment community conservation agreement (CCA) in 2001 was unable to prevent rattan depletion. Then, a local institution called community conservation partnership (CCP) has been recently proposed. Therefore, the objective of this study is to explore how to craft a local institution of CCP for sustainable rattan governance in LLNP using Social-Ecological Systems (SES) Framework. The study was conducted in LLNP area and Ngata Toro, a buffer zone village of LLNP. We conducted rattan inventory and collected social data by interview for analyzing CCP development using SES framework. The results showed that CCP is most likely to be successful in implementing due to several reasons. Firstly, the establishment of constitutional-choice rules made clear the nested enterprise. Secondly, the reallocation of CCP location to the traditional zone increase the boundary clarity. Thirdly, transferring rights to the Ngata Toro community will make effective co-management, increase the legitimacy of rattan utilization, decrease potential conflicts among resource unit users and reducing monitoring cost. Finally, deciding the rattan harvesting quota will ensure the rattan ecological and livelihood sustainability. With the clarity of system boundaries and property rights, we argue that CCP institutions will bring many benefits in many ways. Overall, most variables of SES framework can be used to analyses the readiness of CCP institutional arrangement for sustainable rattan management in LLNP.